Does concomitant autonomous adrenal cortisol overproduction have the potential to confound the interpretation of adrenal venous sampling in primary aldosteronism?. (17th March 2015) - Goupil, Rémi; Wolley, Martin; Ahmed, Ashraf H.; Gordon, Richard D.; Stowasser, Michael
Summary Objective Demonstration of unilateral aldosterone production by adrenal venous sampling (AVS) is required to select appropriate candidates for adrenalectomy in patients with primary aldosteronism (PA). During AVS, aldosterone and cortisol levels are measured to assess successful cannulation and lateralization. In patients with aldosterone‐producing adenoma (APA), concurrent autonomous cortisol secretion might confound AVS results. Design and patients We retrospectively examined results in eight patients with cortisol‐producing adenoma (CPA), but without PA, who underwent AVS. Results In all eight, cortisol was higher on the CPA side than contralateral (CL) (median 6·7‐fold [range 2·4–27·2]; P = 0·012]). By cortisol criteria, CL catheter placement would have been labelled inadequate in six despite adrenal venous aldosterone levels markedly higher than peripheral (41·6‐fold [7·2–510·5]; P < 0·001), suggesting successful cannulation. In all eight, adrenal venous aldosterone/cortisol (A/C) ratios on the CL side were indicative of increased aldosterone production (≥2 times peripheral), but in only three patients on the CPA side (difference CL side 44·5‐fold [6·0–109·0] vs CPA side 1·65‐fold [1·0–23·0]; P = 0·017). A/C ratios were higher on the CL vs the CPA side in seven (20·0‐fold [4·7–76·0]). Conclusion These results in patients with CPA suggest that in patients with APA, concurrent autonomous unilateral cortisol hypersecretion could confound AVS accuracy by increasing cortisol levels (reducing A/C ratio) on the CPA side, while reducing levels (increasing A/C ratio and suggesting failed cannulation) on the CL side. Misclassification of PA subtype or repeat AVS could result, underscoring the importance of adequately assessing cortisol production prior to AVS and the need to consider alternatives.